GE_GERICHTE A/1043/2022 vom 20. Oktober 2022 - GE Cour de justice (2022)
REGROUPEMENT FAMILIAL;CHOSE JUGÉE;MAJORITÉ(ÂGE);RESPECT DE LA VIE FAMILIALE | LEI.44.al1; LEI.47.al1; OASA.73; LEI.47.al4; CEDH.8